Dynamic Control of Orthogonal Upconversion in Migratory Core–Shell Nanostructure toward Information Security. (9th February 2021) - Huang, Jinshu; Yan, Long; Liu, Songbin; Song, Nan; Zhang, Qinyuan; Zhou, Bo
Abstract: Lanthanide‐based materials exhibit abundant emission colors under suitable infrared excitations; however, the dynamic control of orthogonal photon upconversion of lanthanide ions has remained challenging. Here, a novel mechanistic strategy to enable orthogonal upconversion emissions through energy migration in a simple core–shell nanostructure is reported. By constructing the migratory ytterbium‐sublattice shell layer outside the luminescent erbium matrix, the population of erbium emitters at their intermediate energy levels can be finely manipulated, and the red‐to‐green color‐switchable output has been achieved under separate 980 and 808 (or 1530) nm excitations. More interestingly, a tuning of the excitation pulse width also results in a gradual red‐to‐green color change. The mechanistic role of energy migration over ytterbium sublattice is also examined. A conceptual core–shell model for the excitation‐emission orthogonal upconversion output is provided, which is not only important for the fundamental research of photon upconversion but also helps in exciting new chances for the frontier applications such as information security. Abstract : A novel simple migratory core–shell conceptual model is developed for orthogonal upconversion. The red‐to‐green switchable output is easily achieved by dynamic control of the upconversion through altering the excitation wavelengths (e.g., 980/1530 nm) or using the non‐steady‐state excitation, showing great promise in multilevel information security.